2012
DOI: 10.2217/crc.12.22
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention in patients with genetic risk of colorectal cancers

Abstract: SUMMARY A number of genetic syndromes are known to convey a high risk of colorectal cancer. Current standards of medical practice for these patients involve genetic testing followed by screening and surgical procedures. Pharmaceutical therapies for any of these syndromes are limited in number and are generally not approved by any regulatory body for applications in these genetic groups. This review discusses advances in mechanistic understanding of the disease processes leading to the development of promising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…Clinical work with DFMO has supported this concept, although it has still to reach general acceptance for cancer therapy. Notable encouraging results include positive effects on anaplastic gliomas 81 , ongoing clinical trials on neuroblastoma 82,83 and prevention of colorectal cancer 84,85 . In spite of a recent review that erroneously indicated that clinical trials of DFMO have been abandoned because of its toxicity 86 , the safety and therapeutic value of DFMO is well established.…”
Section: Targeting Of Polyamine Metabolismmentioning
confidence: 99%
“…Clinical work with DFMO has supported this concept, although it has still to reach general acceptance for cancer therapy. Notable encouraging results include positive effects on anaplastic gliomas 81 , ongoing clinical trials on neuroblastoma 82,83 and prevention of colorectal cancer 84,85 . In spite of a recent review that erroneously indicated that clinical trials of DFMO have been abandoned because of its toxicity 86 , the safety and therapeutic value of DFMO is well established.…”
Section: Targeting Of Polyamine Metabolismmentioning
confidence: 99%
“…Aspirin and piroxicam in combination with DFMO have been tested in animal studies and showed promising results [ 74 , 75 ]. A phase II clinical trial with aspirin and DFMO combination therapy to test for adenoma recurrence is underway [ 76 ]. The NSAIDs sulindac and celecoxib have been tested in animals and in clinical trials in combination with DFMO with encouraging outcomes [ 28 , 29 , 30 , 31 , 61 , 62 , 68 , 70 , 77 , 78 ].…”
Section: Colon Cancermentioning
confidence: 99%
“…DFMO is clinically approved for the treatment of infection with a specific species of trypanosome, the parasite responsible for African sleeping sickness (15). DFMO is extremely well tolerated and is actively being studied in clinical trials as a chemopreventive agent in gastrointestinal and other cancers (16,17) and in combination with other agents in the treatment of neuroblastoma and other malignancies (18)(19)(20). The idea of targeting ODC expression and activity at multiple steps, from transcription to stability to activity, is attractive, because the development of resistance to all mechanisms occurring at once is unlikely.…”
Section: Identifying An Effective Drug Targeting Ahr To Reduce Polyammentioning
confidence: 99%